WHAT IS THE PREVALENCE OF DIABETES MELLITUS IN JUBA CITY, SOUTH SUDAN? - Cham, Akway M.; Machuny, Maker Malok; Manot, DhelNhomachot; Makuach Gok, Yohanis Riek; Yeich Jang Ruon, Ohide Peter Abraham; Kulang, Riak Amuor (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Diabetes is an important public health problem, one of the four priorities in noncommunicable diseases (NCDs) recognized as an important cause of premature death and disability. In 2014, the number of cases of diabetes was estimated to be 422 million people in the world, a prevalence of 8.5% among adult population. The prevalence of diabetes in South Sudan in general and in Juba city in particular has not been studied. The estimated prevalence of 7.43% according to world diabetes federation was estimated by extrapolation using the neighboring countries. This study is aimed to determine the prevalence of diabetes mellitus in Juba city among patients visiting Malakia Diabetic Control Center. The prevalence of diabetes was determined using cross-sectional study design by analyzing quantitative secondary data. It was found that the prevalence of diabetes mellitus was 11.8%. By gender, the majority of cases were male (7.2%) compared to female (4.6%). Based on this research finding, it can be concluded that Diabetes Mellitus is increasing in South Sudan. Therefore South Sudan government and its partners should double efforts to establish health centers so that more and regular screening can be done. Health education for high risk group and general population should be carried out routinely.